Konspirasi intelektual Yahudi : belajar Islam dari Yahudi - Nurdi, Herry, 1977- (Jakarta : Cakra Lintas Media, 2010)
On Islamic study by orientalists from the perspective of Indonesian Muslim
Includes bibliographical references (p. 240-250) and index
Keywords: Islam -- Study and teaching -- Indonesia; Islamic religious education -- Indonesia